2021 IFFAS Award for Excellence Winner: Weightbearing Radiographs Reliably Predict Normal Ankle Congruence in Weber B/SER2 and 4a Fractures: A Prospective Case-Control Study. Issue 1 (January 2022) - Gregersen, Martin G.; Molund, Marius
Category: Ankle; Trauma Introduction/Purpose: In Weber B/SER2-4 ankle fractures assessment with weightbearing radiographs to ascertain stability of the ankle mortise has been advised. However, no previous studies report whether this method leads to preservation of normal ankle congruence in ankles deemed stable. The purpose is to evaluate equivalence of ankle congruence of injured ankles after fracture union versus the uninjured side for stable Weber B/SER2 and partially unstable Weber B/SER4a fracture types. Methods: We conducted a prospective, case-control study of 149 patients with an isolated Weber B fracture demonstrating stability on weightbearing radiographs. All participants were treated nonoperatively with a functional orthosis and full weightbearing allowed. Results from gravity stress radiographs classified ankles as SER2 or SER4a fracture types. We defined an equivalence margin in medial clear space difference of 1.0 millimeters. We also evaluated the reliability of obtaining measurements from weightbearing radiographs. Results: No difference in medial clear space between the injured and uninjured ankle could be observed after fracture union for stable Weber B/SER2 (mean difference 0.1 millimeters, 95% confidence interval -0.3 to 0.0, P =.056) or partially unstable Weber B/SER4a fracture types (mean difference 0.0 millimeter, (95% confidence interval -0.1 to 0.1, P =.797). No between group differences could be observed (mean difference 0.0 millimeter, 95% confidence interval -0.2 to 0.2, P=.842). These findings were consistent with equivalence as the higher limit of the confidence intervals for the differences were less than the predefined equivalence margin. Estimated 95% confidence intervals for the intraclass correlation coefficients indicated excellent inter- and intraobserver reliability. Conclusion: We demonstrated that weightbearing radiographs successfully predict preservation of normal ankle congruence when the weightbearing radiograph is deemed stable. Ankle congruence was equivalent comparing stable Weber B/SER2 and partially unstable Weber B/SER4a fracture types. Excellent reproducibility of the method of obtaining medial clear space measurements was demonstrated.